LOCAL KNOWLEDGE SUKU AKIT BENGKALIS - Rosaliza, Mita (Universitas Lancang Kuning, 2018)
The Goals of this research are to identify and analyze the local knowledge of Aikit tribe's society in managing the environment related with the value orientation. Utilization of Mangrove forest by Akit tribe is in separable from the role of knowledge system. The conception of values which are the basis of human acts are stored with in the framework of knowledge. According to Kluckhohn, there are orientation values of culture possessed by society 1) the meaning of human life, 2) the meaning of human relationships with others, 3) the problem of human perception about time, 4) Nature of work, 5) the problem of human relationships with nature. This study describes local knowledge of Akit tribe community inexploiting nature where there is an exchange between the nature of work and the condition of nature damage. Akit tribe utilizes mangrove forest as their livelihood as supplier of mangrove wood at Panglong Arang. This research uses qualitativedescriptive, with 6 informants and 4 key informants. Data obtained through interviews conducted in the Berancah village Bengkalis. The results of this study show that local knowledge of Akit Tribe people based on the concep to value orientation has its own definition according to local aspect. It has a relationship in the pattern of acting in the face of nature, therefore it is necessary to pay attention on local knowledge, especially in the value of the essence of the very closely related work with the existence of mangrove forests, and utilize mangrove timber wisely so that the preservation of forest in the coastal areas are well preserved.